Effect of diets with varying starch content on muscle glycogen concentrations during training and replenishment after highintensity exercise - Mesquita, Vanesa Silva de [UNESP] (2014)
Muscle glycogen is an important energy substrate and a potentially limiting factor of performance in horses. Due to the large number of studies using low-starch, high-fat and fiber concentrates for the management of metabolic diseases, the use of such feeds has become widely popular. However, there is scarce evidence of the effectiveness of such feeds on glycogen maintenance and replenishment. To evaluate the effect of three diets varying in starch content on the maintenance of glycogen leveis during a training period and on repletion of glycogen stores after high-intensity exercise, six previously conditioned Thoroughbred horses were used in a 3 x 3 Latin Square design. Horses were fed (at 1 kg/100kg BW/day) either a high-starch (HS), a moderately starch-rich, high-fat concentrate (MS) or a low-starch, high-fat and fiber concentrate (LS). Forage was fed at 1.25 kg/100 kg BW/day in ali treatments. Horses were trained for three weeks and then underwent three days of strenuous exercise designed to substantially deplete glycogen reserves, and were subsequently observed over four days of recovery. Muscle biopsies were obtained before depletion and at 0, 24, 48 and 72 hours post-depletion. Day one of depletion was an incremental exercise test (IET) and blood was sampled at each speed step for plasma glucose and lactate. During the IET horses wore a loose-fit mask for assessment of Oxygen consumption (V02), Carbon Dioxyde production (VCO2) and Respiratory Exchange Ratio (RER). A submaximal exercise test was performed both before and after depletion of glycogen reserves to verify alterations in energy substrate utilization due to depletion. Plasma glucose, lactate and RER during the IET were not different among treatments. RER during the submaximal exercise test were lower for the LS treatment (P<0.05). Post-depletion RER for HS and MS were different from pre-depletion RER in the submaximal test ...